A combination of dichogamy and herkogamy mediates reproductive success in the desert shrub Zygophyllum fabago. (November 2020) - Naghiloo, Somayeh; Claßen-Bockhoff, Regine
Abstract: Zygophyllum fabago is a species within the arid-adapted family Zygophyllaceae. The species is characterized by the co-occurrence of dichogamy and herkogamy. In order to understand the effect of these two complementary anti-selfing mechanisms in reproductive success, we conducted a detailed study of floral biology in Z. fabago . Our results indicated an incomplete separation of the female and male phases which is referred to as partial dichogamy. We found two floral morphs with distinct stigma position: the Central-morph (C-morph) and the Lateral-morph (L-morph). The stigma-stamen distance in the L-morph was significantly larger than in the C-morph in early, mid, and late male stages indicating a high degree of herkogamy. The amount of pollen load of the L-morph stigma under control and selfing condition was significantly lower than of the C-morph, whereas we found no significance difference of pollen load between C and L-morphs under outcrossing condition. Partial protogyny provided opportunities for delayed selfing. On the other hand, the evolution of lateral herkogamy provided an effective mechanism to regulate the degree of delayed selfing in accordance with the outcrossing possibilities in the environment. A combination of dichogamy and herkogamy, therefore, contribute to reproductive success of the species in unpredictable desert environment. Highlights: We found an incomplete separation of floral phases referred to as partial dichogamy. Partial protogyny provided opportunities for delayed selfing. We found two floral morphs with distinct stigma position. Herkogamy provided a mechanism to regulate the degree of delayed selfing. A combination of dichogamy and herkogamy contribute to reproductive success .